Survey of Plasmid Profiles of Shigella Species Isolated in Malaysia During 1994-2000 - Hoe, C.H.; Yassin, R.M.; Koh, Y.T.; Thong, Kwai Lin (Springer Verlag (Germany), 2005)
Plasmid profiling was used to characterize 219 strains of Shigellaspecies isolated from sporadic cases of shigellosis in Malaysia during the period 1994-2000. Heterogeneous plasmid patterns were observed in all Shigella spp. There was a correlation between plasmid patterns and serotypes of S. flexneri, S. dysenteriaeand S. sonnei. Five common small plasmids (> 20.0 kb) were observed in S. flexneri1b and 2a, whereas six common small plasmids were found in serotype 3a. Some of these plasmids appeared to maintain their existence stably in each individual serotype. Plasmids of size 11.40 and 4.20 kb were present only in S. flexneri2a isolates, whereas the 4.40 kb plasmid was unique for serotype 3a. Large (> 150 kb) or mid-range plasmid (20.0-150 kb) was not observed from any S. flexneri1b isolates. Eighty-nine percent of S. flexneriof various serotypes harboured the plasmid of 3.20 kb. All S. dysenteriaetype 2 isolates harboured the 9.00 kb plasmid, while four common small plasmids were found in S. sonneiisolates. The 2.10 kb plasmid was only seen in S. sonnei. Streptomycin resistance in S. dysenteriaetype 2 and multi-drug resistance in S. sonneimay be associated with the 9.00 and 14.8 kb plasmids, respectively. Plasmid profiling provided a further discrimination beyond serotyping and a useful alternative genotypic marker for differentiation of Shigellaspecies. To the best of our knowledge, this is the first report on the plasmid prevalence of the Malaysian Shigella species.